A low cost 3-DOF force sensing unit design for wrist rehabilitation robots. (October 2021) - Mayetin, Umut; Kucuk, Serdar
Abstract: In this study, a low cost and modular three degree-of-freedom force sensor design is developed for the purposes of wrist rehabilitation. The proposed sensor in this study and the existing sensors in the literature are compared to each other considering nine main topics namely, measurement capability, design purpose, measurement approach, force limits, dimensions, producing & assembly complexity, producing cost, modularity and electronics. The comparison results are given as a table. Considering the sensors developed especially for the purpose of wrist rehabilitation in the literature, the proposed sensor has some advantages as follows: The proposed sensor has i) modular structure, ii) less producing & assembly complexity, iii) low cost and iv) integrated electronic and mechanical structures. A specific experimental setup is also developed for both performing force measurements and control of flexion/extension movements. Linearity, hysteresis and repeatability errors of proposed multi-axis force sensor unit are given as table. A set of force measurements is carried out using this experimental setup. Measurements are illustrated as figures. It can be concluded that the proposed force sensor can be used for human-robot interaction in wrist rehabilitation.